Pengaruh Rekrutmen dan Penempatan Kerja Terhadap Kinerja Karyawan Hotel Alpha Pekanbaru - Refni Sukmadewi; Nanik Yuzalmi (Pelantar Press, 2025)
This research aims to analyze the effect of recruitment and job placement on employee performance at Hotel Alpha Pekanbaru. The research method used is quantitative with a survey approach, involving 35 employees from the Front Office and Housekeeping departments as respondents. Data analysis techniques include validity testing, reliability testing, classical assumptions, and multiple linear regression. The results show that recruitment significantly affects employee performance, while job placement does not have a significant partial effect. However, simultaneously, recruitment and job placement have a significant effect on employee performance with a contribution of 55.6%, while the remaining 44.4% is influenced by other factors not studied. These findings indicate that an effective recruitment strategy is crucial for improving employee performance, while evaluation and adjustment of job placements are necessary to align with employee competencies. Hotel Alpha Pekanbaru is recommended to strengthen the recruitment process and regularly evaluate job placements to optimize overall employee performance